Hybrid nanoparticles effects on the flow of a eyring-powell fluid past a shrinking sheet: [Kesan nanozarah hibrid terhadap aliran bendalir eyring-powell pada permukaan mengecut] - Ishak, Anuar (Penerbit Universiti Kebangsaan Malaysia, 2024)
The effect of hybrid nanoparticles on Eyring-Powell fluid flow over a shrinking sheet with power-law velocity is studied. The suitable similarity transformations are used to transform the governing equations into the similarity equations. The bvp4c solver in MATLAB software is employed to generate the numerical results. The outcomes show that the hybrid nanoparticles raise both the velocity and temperature gradients, which consequently increases the friction at the surface and the rate of heat transfer by 5.01% and 0.59%, respectively, compared with the base fluid. However, these physical quantities are reduced, and the domain of the solutions is affected in the presence of the Eyring-Powell fluid parameters. From the stability analysis, only one of the solutions is stable in the long run.